2008
DOI: 10.1097/brs.0b013e3181657e0d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two Guideline Implementation Strategies on Patient Outcomes in Primary Care

Abstract: Active implementation of the German LBP guideline results in slightly better outcomes during 6 months follow-up than its postal dissemination. Results are more distinct when practice nurses are trained in motivational counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
1
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(107 citation statements)
references
References 30 publications
1
101
1
3
Order By: Relevance
“…Our findings do seem to concur with the findings of some of the earlier work in this area particularly in the moderating effects of age and employment, moderate disability and fear avoidance belief on treatment [27,28]. We identified one further trial which, prima facia, reported that intervention effects differed with gender; but the analysis did not include a formal test for interactions so we excluded it [29]. Our findings about treatment expectations also concur with earlier work [30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings do seem to concur with the findings of some of the earlier work in this area particularly in the moderating effects of age and employment, moderate disability and fear avoidance belief on treatment [27,28]. We identified one further trial which, prima facia, reported that intervention effects differed with gender; but the analysis did not include a formal test for interactions so we excluded it [29]. Our findings about treatment expectations also concur with earlier work [30][31][32].…”
Section: Discussionsupporting
confidence: 93%
“…It also increases the likelihood of following up with referrals to other providers, such as psychologists or physical therapists, who can instruct the patient on self-management strategies. Becker et al [59] showed that a low back pain intervention had stronger effects when provided in conjunction with a nurse-led motivational counseling component compared to the intervention alone or a control group that received information about pain. In addition, Habib and colleagues [60] examined the effect of an assessment and feedback intervention on attendance at pain self-management workshops.…”
Section: Improving Adherence By Increasing Patient Knowledge Motivatmentioning
confidence: 99%
“…49, 60, 62-65, 68, 70, 71  Four studies reported subgroup analyses within individual subgroups rather than between group interaction. 60,66,70,88 We examined the conduct and reporting of subgroups in terms of reporting of interpretation and discussion and found: …”
mentioning
confidence: 99%